Orapronobis - Salvador, Philip; Bonnevie, Dina; Alajar, Gina,t; Brocka, Lino; Special People Productions ([Quezon City] Special People Productions, 1989)
In 1985, in the obscure town of Santa Filomena, the Orapronobis, a cult under the leadership of Kumander Kontra (Roco), murders a foreign priest who gave the last rites to an alleged rebel, who was also executed by the same group. At the success of the 1986 EDSA revolt, political detainees, led by Jimmy Cordero (Salvador), celebrate the fall of the dictatorship. All political prisoners are released, including Jimmy, an ex-priest-turned-underground revolutionary. Not long, after, Jimmy marries a human rights activist, Trixie (Bonnevie). Jimmy becomes an advocate of human rights. Despite Trixie's protests, her brother, Roland (Lorenzo), and Jimmy go on a fact-finding mission to Santa Filomena to investigate the latest crime committed by the Orapronobis. Jimmy meets Esper (Alajar), his ex-girlfriend. He finds out that he has a son with her, Camilo (Herrera). They agree to keep Jimmy's true identity a secret form the boy. Conniving with the military, the Orapronobis step up their acts of terror.
Jimmy's group helps evacuate the townspeople to the town church, then later to Manila. Back in Manila, Jimmy turns down a friend's invitation to rejoin the underground movement. Later, he and Roland are ambushed. Jimmy survives, but Roland does not. He recovers and shortly after that, Trixie gives birth to their child. Soldiers raid the refugee center with a masked man who identifies several of the barrio folk as rebels. The refugees and the human rights activists complain to the government. Esper and her son are abducted by the Orapronobis who accuse Esper of helping the rebels. She is raped and beaten up by Kumander Kontra in front of Camilo. Fighting back, she shoots at Kontra. In a hysterical rage, Kontra goes on a shooting rampage, killing Esper, Camilo and the captured barrio men. Later, the military bring the casualties to the town where Jimmy weeps over the bodies of Esper and his son. The film ends with Jimmy contacting his old colleague from the underground.
Summary from the website: https://www.imdb.com/title/tt0097583/plotsummary?ref_=tt_ov_pl
Title from container.
Director, Lino Brocka; writer, Jose F. Lacaba.
Philip Salvador, Dina Bonnevie, Gina Alajar.
In Tagalog.
VHS
Keywords: Action; Drama; Feature films